Guia para elaboração de Projeto de Segurança Contra Incêndio e Pânico em conformidade com o Corpo de Bombeiros Militar do Ceará - Um exemplo prático - Silva, Vanessa de Oliveira (2021)
With the development of large cities throughout history, new construction techniques have also emerged. These techniques brought with it not only technological evolution, but also an increase in the risk of fire, causing an increasing relevance of fire protection for Brazilian society. This paper aims to develop a technical guide that presents the main parameters for the elaboration of Fire Safety Projects, according to the state legislation of the Ceará Military Fire Brigade. However, for dealing with parameters that are not covered by the aforementioned standards, the Brazilian Norms and Technical Instructions of the São Paulo Fire Department will be adopted as a basis. The methodology to be applied will consist of compiling the relevant technical standards, outlining the procedures to carry out this type of project. At the end of this research, the result obtained is an orientation guide based on a model project, aimed at engineers and architects who seek to work in the area of Fire Safety.